Iniciação à docência no IFAM: contribuições do PIBID para a formação docente em ensino de ciências - Tanaka, Ana Lúcia Drumond (Brasil, 2023)
Teacher training is a recurring approach in production and academic debates. In the quest for quality in teacher training, new ground has been trodden by academic institutions. From this perspective, the Ministry of Education created in 2007, the Institutional Scholarship Program Introduction to Teaching (PIBID). This program provides scholarships for undergraduate students participating initiation of projects to teaching developed by higher education institutions (HEIs) in partnership with basic education schools in the public school system. Due to the importance of that program in 2013, with the change in LDB, was regarded as the country has a Public Policy program, the work that follows aimed to identify its contributions to initial teacher training from the perception of undergraduate fellows program of the Federal Institute of Education, Science and Technology of Amazonas (IFAM). The survey presents qualitative approach which data collection was based on two instruments: a questionnaire and documentary research on the PIBID-IFAM. Questionnaires were administered to 15 fellows from initiation to teaching the IFAM in the year 2013, undergraduate in Chemistry and Biological Sciences. The documentary research was based on the following documents: the first notice of CAPES public selection convening of PIBID (Notice MEC / CAPES / FNDE No. 01/2007), the institutional design PIBID / IFAM and the legal basis of PIBID through LDB No. 9.394 / 1996, Decree No. 7.219 / 2010 and Law No. 12.796 / 2013. The analysis points to the real potential of PIBID, institutional level, confirming their contributions to the initial training of undergraduate and appreciation of the teaching profession in the Basic Education of the public school system. In addition, it was noted that the Programme contributes in a representative way for the construction of teaching knowledge and training of research professor, both in the initial training of undergraduates, and in continuing education, as teachers of basic education, participants of the program, experience moments of reflection about their practice and the practice of their students, which triggers improvements in pedagogical teaching practices.